"Antimicrobial and antiproliferative activity of essential oil, aqueous and ethanolic extracts of Ocimum micranthum Willd leaves" - Isabel O. Caamal-Herrera; Leydi M. Carrillo-Cocom; Diana Y. Escalante-Réndiz; Diana Aráiz-Hernández; José A. Azamar-Barrios (BMC, 2018)
Abstract Background Ocimum micranthum Willd is a plant used in traditional medicine practiced in the region of the Yucatan peninsula. In particular, it is used for the treatment of cutaneous infections and wound healing, however there are currently no existing scientific studies that support these applications. The aim of the present study was to evaluate the antimicrobial and the in vitro proliferative activity (on healthy mammalian cell lines) of the essential oil and extracts (aqueous and ethanolic) of this plant. Methods The minimal inhibitory concentration (MIC) of essential oil and aqueous and ethanolic extracts of Ocimum micranthum leaves against Staphylococcus aureus, Bacillus subtilis, Pseudomonas aeruginosa and Candida albicans was determined using the microdilution technique. The in vitro proliferative activity of human fibroblast (hFB) and Chinese hamster ovary (CHO-K1) cells treated with these extracts was evaluated using the MTT test. The hFB cell line was also evaluated using Trypan Blue assay. Results Candida albicans was more susceptible to the ethanolic extract and the aqueous extract (MIC value of 5 μL/mL and 80 μL/mL respectively). In the case of Staphylococcus aureus, Bacillus subtilis, and Pseudomonas aeruginosa, the MIC of the aqueous and ethanolic extract was 125 μL/mL. The aqueous extract showed a significant (p < 0.05) antiproliferative effect on hFB cells at a concentration of 4%, with cell proliferation percentage values of 73.56% and 20.59% by MTT method and Trypan Blue assay, respectively; the same effect was observed for the ethanolic extract at concentration from 0.06% to 0.25% using MTT method and at a concentration from 0.125% to 0.25% using Trypan Blue assay. In CHO-K1 cells an antiproliferative effect was observed at a concentration of 8% of aqueous extract and from 0.06% to 0.25% of ethanolic extract using the MTT method. Conclusion These assays showed that low concentrations of essential oil and extracts of Ocimum micranthum leaves are sufficient to cause an antiproliferative effect on the hFB cell line but do not produce an antimicrobial effect against the microorganisms evaluated. More studies are necessary to improve understanding of the mechanism of action of the compounds implicated in the bioactivities shown by the crude extracts.